Implementasi dan Analisis Attack Tree pada Aplikasi DVWA Berdasar Metrik Time dan Skill Level - Nugraha, Yadi; Widjajarto, Adityas; Fathinuddin, Muhammad (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Attack trees can be formulated based on the steps of exploitation that occur in web applications. The aim of this research is to understand the relationship between attack trees and exploitation characteristics based on time and skill level metrics. The platform for exploitation testing uses DVWA and is organized into an attack tree. The attack tree is structured with both protected and unprotected WAF conditions. The attack tree is organized based on five vulnerabilities: SQL Injection, XSS (Reflected), Command injection, CSRF, and Brute force. The analysis results with the unprotected WAF condition conclude that the XSS (Reflected) attack tree ranks first with a score of 131.92. The SQL Injection attack tree ranks last with a score of 1727.56. Meanwhile, with the WAF, the SQL Injection attack tree ranks first with a score of 54. The Brute force attack tree ranks last with a score of 319.51. Thus, this relationship can be used for ranking attack trees based on time and skill level metrics. Further research can involve detailing the steps of exploitation using CVSS scores as a skill level calculation and measuring parameters using IDS as one of the firewall features.